1999
DOI: 10.1093/ajcn/69.6.1135
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of saturated and monounsaturated fatty acids on postprandial lipemia and incretin responses in healthy subjects

Abstract: Background: Elevations of postprandial triacylglycerol-rich plasma lipoproteins and suppressions of HDL-cholesterol concentrations are considered potentially atherogenic. Long-term studies have shown beneficial effects of monounsaturated fatty acids (eg, oleic acid) on fasting lipid and lipoprotein concentrations in humans. A direct stimulatory effect of oleic acid on the secretion of glucagon-like peptide 1 (GLP-1) was shown in animal studies. Objective: We compared the postprandial responses of glucose, insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
188
9
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 280 publications
(218 citation statements)
references
References 44 publications
12
188
9
3
Order By: Relevance
“…To summarize the important number of studies performed (reviewed by Williams, 1997;Roche et al, 1998a;Thomsen et al, 1999;Mekki et al, 2002), short or medium dietary fatty acids lower postprandial lipid response by mostly entering the portal route instead of chylomicron secretion. Dairy fats contain significant amounts of short-and medium-chain fatty acids.…”
Section: Dietary Fatty Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…To summarize the important number of studies performed (reviewed by Williams, 1997;Roche et al, 1998a;Thomsen et al, 1999;Mekki et al, 2002), short or medium dietary fatty acids lower postprandial lipid response by mostly entering the portal route instead of chylomicron secretion. Dairy fats contain significant amounts of short-and medium-chain fatty acids.…”
Section: Dietary Fatty Acidsmentioning
confidence: 99%
“…Dairy fats contain significant amounts of short-and medium-chain fatty acids. Most studies have shown that saturated, monounsaturated and n-6 polyunsaturated fatty acids (PUFAs) do not generally elicit markedly different postprandial lipid responses (de Bruin et al, 1993;Lichtenstein et al, 1993;Tholstrup et al, 2001;Mekki et al, 2002), while some studies report exacerbated (Thomsen et al, 1999) or reduced (Mekki et al, 2002) responses after intake of saturated butter fat. More recently, studies that have measured changes in different lipoprotein subfractions have revealed important differences with lipemic responses being of the order saturated fatty acid (SFA)4monounsaturated fatty acid (MUFA)4PUFA (Jackson et al, 2002a, b;Jackson et al, 2005).…”
Section: Dietary Fatty Acidsmentioning
confidence: 99%
“…Some conflicting data on the type of dietary fatty acids and their effects on insulin secretion are available from meal and dietary intervention studies. In humans, no differences in insulin responses were found after meals [39,40] or longterm diets [41], which were high in monounsaturated or saturated fatty acids. Some studies have reported greater stimulation of insulin secretion after diets high in saturated fatty acids in subjects with Type II diabetes [42] and normal rats [43] but others have reported a more pronounced effect with polyunsaturated fatty acids [44].…”
Section: Discussionmentioning
confidence: 99%
“…This could be the result of a slower intestinal absorption of saturated fatty acids [51]. After a mixed meal, the plasma GLP-1 increase has also been shown to be more pronounced with the presence of olive oil than palm oil or butter in healthy humans [39]. Also, in vitro, oleic acid is a stronger stimulator of GLP-1 secretion than saturated fatty acids [52].…”
Section: Discussionmentioning
confidence: 99%
“…The potential role of GLP-1 in the regulation of appetite and food intake (Flint et al, 1998;Gutzwiller et al, 1999) and the potential role of GLP-1 and GIP of lipid metabolism (Thomsen et al, 1999) have been investigated recently. A positive correlation between the postprandial GIP response and the subjective satiety sensation was observed in healthy normal weight subjects (Raben et al, 1996).…”
Section: Introductionmentioning
confidence: 99%